2023
DOI: 10.1186/s40594-023-00426-7
|View full text |Cite
|
Sign up to set email alerts
|

Face negotiation in graduate school: the decision to conceal or reveal depression among life sciences Ph.D. students in the United States

Abstract: Background Depression is one of the top mental health concerns among biology graduate students and has contributed to the “graduate student mental health crisis” declared in 2018. Several prominent science outlets have called for interventions to improve graduate student mental health, yet it is unclear to what extent graduate students with depression discuss their mental health with others in their Ph.D. programs. While sharing one’s depression may be an integral step to seeking mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Finally, we hope these findings will help program directors, advisors, and graduate student peers better assess which students might be at higher risk of poor mental health and refer those students to appropriate services. Recent research has shown that over half of life science graduate students with depression revealed their mental health status to their advisor and almost three quarters revealed it to a peer [58]. Our study suggests, however, that graduate students may not always label mental health problems as such.…”
Section: Plos Onecontrasting
confidence: 56%
“…Finally, we hope these findings will help program directors, advisors, and graduate student peers better assess which students might be at higher risk of poor mental health and refer those students to appropriate services. Recent research has shown that over half of life science graduate students with depression revealed their mental health status to their advisor and almost three quarters revealed it to a peer [58]. Our study suggests, however, that graduate students may not always label mental health problems as such.…”
Section: Plos Onecontrasting
confidence: 56%
“…, 2020 ). Like graduate students with depression, Christian undergraduate students’ were more likely to reveal their religious identity to peers who they had a closer personal relationship with ( Wiesenthal et al. , 2023 ).…”
Section: Resultsmentioning
confidence: 99%